Correction: Bipolarons rule the short-range terahertz conductivity in electrochemically doped P3HT. Issue 2 (10th January 2022) - Tsokkou, Demetra; Cavassin, Priscila; Rebetez, Gonzague; Banerji, Natalie
Abstract : Correction for 'Bipolarons rule the short-range terahertz conductivity in electrochemically doped P3HT' by Demetra Tsokkou et al., Mater. Horiz., 2022, DOI: ; 10.1039/d1mh01343b .